Trends and Characteristics of CDC Global Rapid Response Team Deployments—A 6-Month Report, October 2018–March 2019. (May 2020) - Ben Hamida, Amen; Bugli, Dante; Hoffman, Adela; Greiner, Ashley L.; Harley, Danny; Saindon, John M.; Walsh, James; Bierman, Eli; Mallory, Jonathon; Blaylock, Kenneth; Shetty, Sharmila; Bensyl, Diana M.; et al.
The Centers for Disease Control and Prevention (CDC) Global Rapid Response Team (GRRT) was launched in June 2015 to strengthen the capacity for international response and to provide an agency-wide roster of qualified surge-staff members who can deploy on short notice and for long durations. To assess GRRT performance and inform future needs for CDC and partners using rapid response teams, we analyzed trends and characteristics of GRRT responses and responders, for deployments of at least 1 day during October 1, 2018, through March 31, 2019. One hundred twenty deployments occurred during the study period, corresponding to 2645 person-days. The median deployment duration was 19 days (interquartile range, 5-30 days). Most deployments were related to emergency response (n = 2367 person-days, 90%); outbreaks of disease accounted for almost all deployment time (n = 2419 person-days, 99%). Most deployments were to Africa (n = 1417 person-days, 54%), and epidemiologists were the most commonly deployed technical advisors (n = 1217 person-days, 46%). This case study provides useful information for assessing program performance, prioritizing resource allocation, informing future needs, and sharing lessons learned with other programs managing rapid response teams. GRRT has an important role in advancing the global health security agenda and should continuously be assessed and adjusted to new needs.